Characterization of Basal Transcriptomes Identifies Potential Metabolic and Virulence-Associated Adaptations Among Diverse Nontyphoidal Salmonella enterica Serovars - Cohn, Alexa R.; Orsi, Renato H.; Carroll, Laura M.; Chen, Ruixi; Wiedmann, Martin; Cheng, Rachel A. (Frontiers in Microbiology, 2021)
The zoonotic pathogen Salmonella enterica includes >2,600 serovars, which differ in the range of hosts they infect and the severity of disease they cause. To further elucidate the mechanisms behind these differences, we performed transcriptomic comparisons of nontyphoidal Salmonella (NTS) serovars with the model for NTS pathogenesis, S. Typhimurium. Specifically, we used RNA-seq to characterize the understudied NTS serovars S. Javiana and S. Cerro, representing a serovar frequently attributed to human infection via contact with amphibians and reptiles, and a serovar primarily associated with cattle, respectively. Whole-genome sequence (WGS) data were utilized to ensure that strains characterized with RNA-seq were representative of their respective serovars. RNA extracted from representative strains of each serovar grown to late exponential phase in Luria-Bertani (LB) broth showed that transcript abundances of core genes were significantly higher (p < 0.001) than those of accessory genes for all three serovars. Inter-serovar comparisons identified that transcript abundances of genes in Salmonella Pathogenicity Island (SPI) 1 were significantly higher in both S. Javiana and S. Typhimurium compared to S. Cerro. Together, our data highlight potential transcriptional mechanisms that may facilitate S. Cerro and S. Javiana survival in and adaptation to their respective hosts and impact their ability to cause disease in others. Furthermore, our analyses demonstrate the utility of omics approaches in advancing our understanding of the diversity of metabolic and virulence mechanisms of different NTS serovars.